The Influence of Internship Experience, Work Interest, and Self-Efficacy on Work Readiness (Case Study of Management Students Class of 2018-2020, Faculty of Economics and Business, University of Riau) - Dilla, Alda Zahra; Hendriani, Susi; Pramadewi, Arwinence (Journal Of Accounting Management Business And International Research, 2024)
This study aims to look at internship experience, job interest, and self-efficacy on job readiness (case study of management students class 2018-2020 faculty of economics and business, Riau University). The population in the study were students majoring in management at the Faculty of Economics and Business, University of Riau class of 2018-2020) who have participated in internships with a total of 517 people. The sampling technique used is proportional stratified random sampling, which is the activity of taking samples from the population if the population is not homogeneous (not the same) and there are levels (stratified) proportionally, so that the sample in this study amounted to 84 people. The data analysis method used is multiple liner regression analysis using the help of the SPSS Version 26 program. The results showed that there was a positive and significant influence between internship experience on job readiness. There is a positive and significant influence between job interest on job readiness. There is a positive and significant influence between self-efficacy on job readiness. There is a positive and significant influence simultaneously between internship experience, job interest, and self-efficacy on job readiness.